Pengaturan Hukum Penyalahgunaan AI (Artificial Intelligence) dalam Peniruan Suara atau Voice Cloning terhadap Tindakan Penipuan - Putu Riskha Puspita Dewi (Lembaga Pengembangan Kinerja Dosen, 2025)
The increasingly advanced era is certainly followed by various developments in the fields of economy, social, culture and even technology. Technological progress in various countries can be seen from the existence of a technology called AI. Artificial Intelligence or AI is an artificial intelligence technology that has the ability to solve problems like humans. In practice, AI will simulate human intelligence with the ability to recognize images, write and even make predictions based on data. Lately, AI has begun to be misused by individuals who feel they are benefiting. In Indonesia, the misuse of AI technology has been rampant where perpetrators use AI for fraud. An act that uses technology as the main weapon of crime is included in the category of cyber crime. The rampant case of cyber crime in Indonesia is the act of voice imitation or voice cloning. The perpetrators in committing their crimes usually use a technological intermediary that can change their voice so that it is similar to the voice of relatives, friends, family or important people or public figures recognized by the victim. Voice imitation or known as voice cloning is the ability to imitate a voice that is similar to the original voice. Voice cloning using AI technology is an imitation of the human voice with an extraordinary level of accuracy of similarity, both in intonation, tone, and also voice patterns. The law on information and electronic transactions contains various regulations regarding information and electronic transactions, but the law does not explain in detail the misuse of AI in voice cloning because there are still limitations in the ITE law regarding criminal acts of voice cloning fraud and until now criminal acts of voice cloning are still rampant.